GAMBARAN KEPUASAN KERJA KARYAWAN PT. WORLEYPARSONS INDONESIA DI TINJAU DARI TEORI DUA FAKTOR HERZBERG - Bestyana Beliadwi; Clara Moningka (Universitas Bunda Mulia, 2012)
This research was conducted to see the picture of employee satisfaction in terms of Herzberg's two-factor theory in PT. WorleyParson Indonesia Jakarta. Based on the initial survey conducted by researchers, it was found that the job satisfaction experienced by employees working.From the above researchers are interested to see how the picture of employee satisfaction in terms of the theory of two factors. In this study the researchers used Herzberg's theory of job satisfaction, Locke, Robbins and others. While the theory of two factors used is the theory advanced by Frederick Herzberg (1959). Job satisfaction questionnaire prepared by Sulastri (2010) based on two-factor theory of Herzberg (1959). The statistical method used in this research is quantitative research methods with the calculation of descriptive statistics. Variables taken from job satisfaction questionnaire developed by Sulastri (2010) based on Herzberg's two-factor theory and interviews. Items are 40 item questionnaire. In this study of employees who are willing to fill the job satisfaction questionnaire totaled 133 people of the total sample of 200 employees were interviewed and of six employees. From the results of this study found that employees generally have a tendency to job satisfaction by factors present in the theory of two factors: motivation factors and hygiene factors. In connection with it could be concluded that there is a tendency of employees were satisfied with their jobs.Keywords: human resources, employee job satisfaction. Herzberg's two-factor theory